Release-modulating acetylcholine receptors in cholinergic neurones of the guinea-pig ileum. - Fosbraey, P. (Nature Publishing Group, 1980)
1 Twitch responses of the guinea-pig ileum to electrical transmural stimulation (0.2 Hz) were smaller after a dose of acetylcholine (ACh) than before it. The magnitude of the post-ACh inhibition of twitch was dose-dependent. 2 The post-ACh inhibition of twitch could not be explained in terms of post-junctional desensitization and was not modified by guanethidine, thymoxamine, propranolol or naloxone. Inhibition of twitch also followed high frequency stimulation (10 Hz) but this inhibition, unlike that following ACh, was partially antagonized by naloxone. 3 Hexamethonium (C6) in concentrations known to block contractions to nicotine, potentiated the post-ACh inhibition of twitch and modified the pattern of recovery. An initial rapid phase followed by a slower phase was converted by C6 to an initial slow phase followed by a more rapid rate of recovery. 4 The C6-sensitive (nicotinic) component of twitch recovery after ACh was also dose-dependent and contributed greatly to the rapid recovery during the first minute after ACh washout, whereas during the same period the C6-resistant inhibition remained relatively constant; thereafter both components declined. The C6-resistant inhibition was considered to be due to the activation of prejunctional muscarinic receptors. 5 5-Hydroxytryptamine (5-HT) and nicotine also caused inhibition of twitch but the pattern of response differed from those due to ACh, the maximum inhibition usually being produced 1 min after recommencing stimulation. High doses of 5-HT produced inhibitory responses similar to those following ACh, whereas nicotine produced a characteristic triphasic pattern of response. 6 It is concluded that ACh acts on at least two prejunctional receptors subserving a modulatory role on transmitter release, a nicotinic receptor whose activation enhances ACh output and a muscarinic receptor whose activation leads to an inhibition of transmitter secretion.